The state policy in the field of school education in the Soviet Russia in 1917–1923 - Slobodian, Stanislav (Biuletyn Historii Wychowania, 2017)
This article reviews Bolshevik policy in the field of school education in the early years of Soviet power. The author draws attention to the ideological and political differences between the party and most of the teachers, which intensified after the Bolsheviks seized power. The atmosphere of mutual distrust negatively affected the social policies concerning teachers at the local level. The terrible financial situation of the teachers led to a critical shortage of staff, a decrease in the overall competence of school employees, lack of motivation and capacity to effectively implement school reform. At the same time, the authorities significantly increased the requirements for teachers. Therefore, the Bolsheviks’ concept of the “labour school” was implemented with considerable distortions, causing a general decline in the quality of school education. Summing up the experience of school policy in the first years of the Soviet power, the Bolsheviks understood the need to review their attitude to people’s teachers and in particular to the remuneration of their labour.